SAMPLING DENSITY FOR CHARACTERIZING THE PHYSICAL QUALITY OF A SOIL UNDER COFFEE CULTIVATION IN SOUTHWESTERN MINAS GERAIS - Silvero, Nelda E. Q. [UNESP]; Marques Junior, Jose [UNESP]; Siqueira, Diego S. [UNESP]; Gomes, Romario P. [UNESP]; Costa, Milene M. R. [UNESP] (Soc Brasil Engenharia Agricola, 2018)
The elaboration of maps to characterize the spatial variability of soil attributes assists in the strategic planning and decision making of agricultural managers. Precision and accuracy of maps are related to the ideal sampling density to characterize the variability pattern. This study was conducted with the aim of identifying the sampling density to represent the variability of soil physical quality using attributes with different magnitudes of variation in an area cultivated with coffee. Three approaches were used to find the most adequate sampling density (geostatistical analysis, percentage of error associated with the sampling density, and coefficient of variation). A total of 145 soil samples were collected at a depth of 0-0.20 m at the crossing points of a regular grid with a spacing of 50 m. The percentage of clay, silt, and sand, macroporosity, microporosity, total pore volume, and soil density were determined. The data were submitted to descriptive statistical analysis. For elaborating the variability maps with up to 15% error and soil attributes with a coefficient of variation close to 50%, a sampling density of 3 points ha(-1) is suggested.
Keywords: precision agriculture; Coffea arabica; sampling error; geostatistic